The Silent Side of Academia: A Bibliometric Study of Knowledge Hiding - Yang, Kaiyu (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Knowledge hiding has received increasing scholarly attention in organizational research, yet its development within academic settings remains fragmented and insufficiently synthesized. This study provides a comprehensive bibliometric analysis of research on knowledge hiding in academia to clarify the field’s intellectual structure, thematic evolution, and emerging research directions. Using a systematic literature review protocol, 39 Scopus-indexed publications were identified and analyzed through established bibliometric techniques. Following recommended procedures, the analysis combines performance indicators with science mapping methods to examine publication trends, influential authors, sources, and institutions, as well as the conceptual structure of the domain. Keyword co-occurrence and thematic mapping were applied to identify dominant research clusters and evolving themes.           The results reveal a rapidly developing but still nascent research field, with increasing scholarly attention since the late 2010s. The literature is primarily grounded in organizational behavior and knowledge management perspectives, emphasizing leadership dynamics, interpersonal relationships, competitive climates, and individual psychological factors that shape knowledge concealment in academic settings. Science mapping further highlights the central role of relational and contextual factors in explaining knowledge hiding behaviors within academia.          By systematically mapping the knowledge base of this emerging research area, the study advances understanding of knowledge hiding among academics and identifies key avenues for future theoretical and empirical development.